Regional monitoring of the urinary tract infections etiological spectrum pathogens in the child population in Chernivtsi region: dynamic changes, age, gender, administrative and territorial characteristics - V. V. Bezruk; T. О. Bezruk; O. R. Babiy; S. O. Sokolnyk; M. I. Sheremet; V. V. Maksymyuk; O. I. Godovanets; O. S. Godovanets; A. I. Kovtun (Zaporožskij Medicinskij Žurnal)
Microbiological monitoring of the uropathogens is an effective «tool» for urinary tract infectious and inflammatory diseases treatment quality improvement.